Analysis of The Impact of the Role of Halal Authority on the Economy - Nurfala Safitri; Maya Panorama; Muhammad Abdul Rohman (Asyafina Journal: Jurnal Akademi Pesantren, 2022)
Halal Value Chain has an essential role in a country, but many countries ignore halal authority. In addition, based on the results of previous research studies discussing halal authority have shown that halal source can reduce information asymmetry in a product. Muslims around the world everyone needs this. This study aims to determine the relationship between a dynamic transformation which includes three sectors contributing services, agriculture, and industry, with the halal authority in a country. This study uses panel data consisting of 228 countries. Of the whole countries, only 45 countries have halal control. This data processing process uses stata. This study uses a static panel analysis method, namely the random effect model, common effect regression, and dynamic panels. The results of this study state that the existence of a halal value chain affects the transformation of a country that details halal authorities to have a significant relationship to service contributions, halal authorities have a significant relationship to agricultural contributions, halal authorities have a significant relationship to industry contributions to Gross Domestic Product (GDP) by including control variables such as access electricity, individual using the internet, domestic credit to the private sector, household and final consumption expenditure. Data and Material can access at: https://doi.org/10.7910/DVN/8BRLJL